Associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 with molecular subtypes, PD-L1 expression, and FGFR3 mutational status in two advanced urothelial bladder cancer cohorts - Bahlinger, Veronika; Branz, Annalena; Strissel, Pamela; Strick, Reiner; Lange, Fabienne; Geppert, Carol-Immanuel; Klümper, Niklas; Hölzel, Michael; Wach, Sven; Taubert, Helge; Sikic, Danijel; Wullich, Bernd; et al. (Histopathology, 2024)
Aims: Treatment options for advanced urothelial carcinoma (aUC) rapidly evolved: besides immunomodulative therapeutic options and inhibitors targeting Fibroblast growth factor receptor (FGFR) alterations, two new antibody-drug conjugates (ADC), sacituzumab govitecan (SG) and enfortumab vedotin (EV), have been approved. However, little is known about the associations of specific aUC properties and the surface target expression of TROP2 and NECTIN-4. Our aim was to characterize associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 protein and gene expression with morphomolecular and clinicopathological characteristics of aUC in two large independent cohorts. Methods and results: The TCGA BLCA (n = 405) and the CCC-EMN (n = 247) cohorts were retrospectively analysed. TROP2/TACSTD2 and NECTIN-4/NECTIN-4 are highly expressed at the protein and transcript level in aUC, and their expression status did not correlate with patient survival in both cohorts. NECTIN-4/NECTIN-4 expression was higher in luminal tumours and reduced in squamous aUCs. NECTIN-4 was negative in 10.6% of samples, and 18.4% of samples had low expression (H-score <15). The TROP2 negativity rate amounted to 6.5%. TACSTD2 and NECTIN-4 expression was reduced in neuroendocrine-like and/or protein-based double-negative tumours. TROP2- and NECTIN-4-negative tumours included one sarcomatoid and four neuroendocrine aUC. FGFR3 alterations and PD-L1 expression on tumour and immune cells did not associate with TROP2 or NECTIN-4 expression. Conclusions: TACSTD2/TROP2 and NECTIN-4/NECTIN-4 are widely expressed in aUC, independent of FGFR3 alterations or PD-L1 expression, thus representing a suitable target for ADC treatment in the majority of aUC. The expression loss was associated with aggressive morphomolecular aUC subtypes, i.e. neuroendocrine(-like) and sarcomatoid aUC.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Advanced urothelial carcinoma; membranous expression; NECTIN-4/NECTIN-4; TACSTD2/TROP2; treatment options

Bladder tumor subtype commitment occurs in carcinoma in-situ driven by key signaling pathways including ECM remodeling - Wullweber, Adrian; Strick, Reiner; Lange, Fabienne; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Bertz, Simone; Weyerer, Veronika; Stöhr, Robert; Breyer, J.; Burger, M.; et al. (EUROPEAN UROLOGY, 2021)
CRIS-Team WoS Importer:2021-08-20

Bladder Tumor Subtype Commitment Occurs in Carcinoma In Situ Driven by Key Signaling Pathways Including ECM Remodeling - Wullweber, Adrian; Strick, Reiner; Lange, Fabienne; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Bertz, Simone; Weyerer, Veronika; Stöhr, Robert; Breyer, Johannes; Burger, Maximilian; et al. (Cancer Research, 2021)
Basal and luminal subtypes of invasive bladder tumors have significant prognostic and predictive impacts for patients. However, it remains unclear whether tumor subtype commitment occurs in noninvasive urothelial lesions or in carcinoma in situ (CIS) and which gene pathways are important for bladder tumor progression. To understand the timing of this commitment, we used gene expression and protein analysis to create a global overview of 36 separate tissues excised from a whole bladder encompassing urothelium, noninvasive urothelial lesions, CIS, and invasive carcinomas. Additionally investigated were matched CIS, noninvasive urothelial lesions, and muscle-invasive bladder cancers (MIBC) from 22 patients. The final stage of subtype commitment to either a luminal or basal MIBC occurred at the CIS transition. For all tissues combined, hierarchical clustering of subtype gene expression revealed three subtypes: "luminal," "basal," and a "luminal p53-/extracellular matrix (ECM)-like" phenotype of ECM-related genes enriched in tumor-associated urothelium, noninvasive urothelial lesions, and CIS, but rarely invasive, carcinomas. A separate cohort of normal urothelium from noncancer patients showed significantly lower expression of ECM-related genes compared with tumor-associated urothelium, noninvasive urothelial lesions, and CIS. A PanCancer Progression Panel of 681 genes unveiled pathways specific for the luminal p53-/ECM-like cluster, for example, ECM remodeling, angiogenesis, epithelial-to-mesenchymal transition, cellular discohesion, cell motility involved in tumor progression, and cell proliferation and oncogenic ERBB2/ERBB3 signaling for invasive carcinomas. In conclusion, this study provides insights into bladder cancer subtype commitment and associated signaling pathways, which could help predict therapy response and enhance our understanding of therapy resistance.
CRIS-Team WoS Importer:2021-04-09

Cytotoxic T-cell-related gene expression signature predicts improved survival in muscle-invasive urothelial bladder cancer patients after radical cystectomy and adjuvant chemotherapy - Eckstein, Markus; Strissel, Pamela; Strick, Reiner; Weyerer, Veronika; Wirtz, Ralph; Pfannstiel, Carolin; Wullweber, Adrian; Lange, Fabienne; Erben, Philipp; Stöhr, Robert; Bertz, Simone; Geppert, Carol-Immanuel; et al. (Journal for ImmunoTherapy of Cancer, 2020)
Background Assessment of the immune status of muscle-invasive bladder cancer (MIBC) has previously shown to be prognostically relevant after treatment with curative intent. We conducted this study to develop a clinically applicable immune gene expression assay to predict prognosis and adjuvant chemotherapy benefit. Patients and methods Gene expression of CD3Z, CD8A and CXCL9, immune cell (IC) populations including stromal tumor infiltrating lymphocytes (sTILs), T-cells, natural killer cells (NK-cells), macrophages, Programmed cell death protein 1 positive (PD-1) IC and tumor subtypes (MD Anderson Cancer Center/MDACC-approach) were assessed in 187 MIBC patients (Comprehensive Cancer Center Erlangen-EMN/CCC-EMN-cohort). A gene expression signature was derived by hierarchical-clustering and validated in The Cancer Genome Atlas (TCGA)-cohort. IC populations in the TCGA cohort were assessed via CIBERSORT. Benefit of platinum-containing adjuvant chemotherapy was assessed in a pooled cohort of 125 patients. Outcome measurements were disease specific survival, disease-free survival and overall survival. Results The gene expression signature of CXCL9, CD3Z and CD8A correlates with quantitative amounts of specific IC populations and sTILs (CCC-EMN: ρ-range: 0.44-0.74; TCGA: ρ-range: 0.56-0.82) and allows stratification of three different inflammation levels (inflamed high, inflamed low, uninflamed). Highly inflamed tumors are preferentially basal subtype and show favorable 5-year survival rates of 67.3% (HR=0.27; CCC-EMN) and 55% (HR=0.41; TCGA). Uninflamed tumors are predominantly luminal subtypes and show low 5-year survival rates of 28% (CCC-EMN) and 36% (TCGA). Inflamed tumors exhibit higher levels of PD-1 and Programmed cell death 1 ligand 1 (PD-L1). Patients undergoing adjuvant platinum-based chemotherapy with 'inflamed high' tumors showed a favorable 5-year survival rate of 64% (HR=0.27; merged CCC-EMN and TCGA cohort). Conclusion The gene expression signature of CD3Z, CD8A and CXCL9 can assess the immune status of MIBC and stratify the survival of MIBC patients undergoing surgery and adjuvant platinum-based chemotherapy. Furthermore, the assay can identify patients with immunological hot tumors with particular high expression of PD-L1 potentially suitable for immunotherapy.
CRIS-Team Scopus Importer:2020-06-05
Keywords: immunology; pathology; urology

Das muskelinvasive und metastasierte Urothelkarzinom der Harnblase: Aktueller Stand histopathologischer, molekularer und immunologischer Prognose- und Prädiktionsfaktoren - Bertz, Simone; Bahlinger, Veronika; Lange, Fabienne; Hartmann, Arndt; Eckstein, Markus (Die Pathologie, 2024)
Background: Muscle-invasive and metastatic urothelial carcinoma (UC) represents a heterogeneous disease entity with numerous morphological, molecular, and immunological phenotypes. Aims: This article aims to provide an overview of current histopathological, molecular, and immunological prognostic and predictive factors in muscle-invasive and metastatic UC. Results and discussion: Muscle-invasive and metastatic UC exhibits a wide range of divergent differentiations and histological subtypes. The correct diagnosis of these morphological variants is essential, as they may determine the clinical course and may also present specific and potentially therapeutically targetable molecular alterations (e.g., HER2 alterations in micropapillary UC). The morphological subtypes largely correlate with the six molecular consensus subtypes. Furthermore, morphological and molecular subtypes are associated with immunological properties that are relevant for modern immunotherapies, such as the PD-L1 status. Numerous immunotherapy studies in the setting of curatively treatable muscle-invasive UC will be reported in 2024 and 2025, likely leading to an increasing number of PD-L1 testing indications.
CRIS-Team Scopus Importer:2024-08-16
Keywords: B7-H1 antigen; Disease progression; Immunotherapy; Molecular pathology; Transitional cell carcinoma

Digital volumetric assessment of CIS and tumor mass compliments conventional histopathological assessment in muscle-invasive urothelial bladder cancer - Lange, Fabienne; Geppert, Carol-Immanuel; Bahlinger, Veronika; Bertz, Simone; Stöhr, Robert; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Hartmann, Arndt; Eckstein, Markus (Virchows Archiv, 2024)
Carcinoma in situ (CIS) of the bladder is a known parameter regarding the prognosis and recurrence tendency of urothelial carcinomas. Nevertheless, there is little evidence whether the amount of CIS or other precursor lesions, as well as the quantified tumor mass of muscle-invasive urothelial carcinoma, has an influence on the survival or recurrence rate of affected patients. From 80 patients with muscle invasive urothelial bladder cancer and radical cystectomy, 23 samples each were obtained as part of a whole organ mapping in a single institution study, in which the precursor lesions and tumor area were digitally measured and further correlated to pathological standard parameters, patient survival, molecular luminal and basal subtypes, and immune infiltration. Significant correlations were found between tumor mass and surface lining CIS amount for pT-stage, lymphovascular invasion, and perineural infiltration. Furthermore, an increased tumor mass as well as an increased amount of CIS combined with an increased tumor mass showed a significantly reduced survival rate in multivariable analysis (HR = 2.75; P = 0.019 vs. HR = 3.54; P = 0.002) as well as a significantly increased recurrence. No correlations could be found with molecular subtypes and immune infiltration. The exact measurement of the tumor mass with and without the CIS surface area, whether manually or, more specifically, digitally, could be incorporated into routine diagnostics and implemented as an independent predictor for patient post-surgical outcomes. It can therefore serve as an additional predictor for risk stratification and, if necessary, intensified follow-up care or therapy.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Muscle invasive bladder cancer; Prognosis; Radical cystectomy; Survival; Urothelial carcinoma; Urothelial carcinoma in situ

First report from the German COVID-19 autopsy registry - von Stillfried, Saskia; Bülow, Roman David; Röhrig, Rainer; Boor, Peter; Böcker, Jana; Schmidt, Jens; Tholen, Pauline; Majeed, Raphael; Wienströer, Jan; Weis, Joachim; Bremer, Juliane; Knüchel, Ruth; et al. (The Lancet Regional Health - Europe, 2022)
Background: Autopsies are an important tool in medicine, dissecting disease pathophysiology and causes of death. In COVID-19, autopsies revealed e.g., the effects on pulmonary (micro)vasculature or the nervous system, systemic viral spread, or the interplay with the immune system. To facilitate multicentre autopsy-based studies and provide a central hub supporting autopsy centres, researchers, and data analyses and reporting, in April 2020 the German COVID-19 Autopsy Registry (DeRegCOVID) was launched. Methods: The electronic registry uses a web-based electronic case report form. Participation is voluntary and biomaterial remains at the respective site (decentralized biobanking). As of October 2021, the registry included N=1129 autopsy cases, with 69271 single data points including information on 18674 available biospecimens gathered from 29 German sites. Findings: In the N=1095 eligible records, the male-to-female ratio was 1·8:1, with peaks at 65-69 and 80-84 years in males and >85 years in females. The analysis of the chain of events directly leading to death revealed COVID-19 as the underlying cause of death in 86% of the autopsy cases, whereas in 14% COVID-19 was a concomitant disease. The most common immediate cause of death was diffuse alveolar damage, followed by multi-organ failure. The registry supports several scientific projects, public outreach and provides reports to the federal health authorities, leading to legislative adaptation of the German Infection Protection Act, facilitating the performance of autopsies during pandemics. Interpretation: A national autopsy registry can provide multicentre quantitative information on COVID-19 deaths on a national level, supporting medical research, political decision-making and public discussion. Funding: German Federal Ministries of Education and Research and Health. Hintergrund: Obduktionen sind ein wichtiges Instrument in der Medizin, um die Pathophysiologie von Krankheiten und Todesursachen zu untersuchen. Im Rahmen von COVID-19 wurden durch Obduktionen z.B. die Auswirkungen auf die pulmonale Mikrovaskulatur, das Nervensystem, die systemische Virusausbreitung, und das Zusammenspiel mit dem Immunsystem untersucht. Um multizentrische, auf Obduktionen basierende Studien zu erleichtern und eine zentrale Anlaufstelle zu schaffen, die Obduktionszentren, Forscher sowie Datenanalysen und -berichte unterstützt, wurde im April 2020 das deutsche COVID-19-Autopsieregister (DeRegCOVID) ins Leben gerufen. Methoden: Das elektronische Register verwendet ein webbasiertes elektronisches Fallberichtsformular. Die Teilnahme ist freiwillig und das Biomaterial verbleibt am jeweiligen Standort (dezentrales Biobanking). Im Oktober 2021 umfasste das Register N=1129 Obduktionsfälle mit 69271 einzelnen Datenpunkten, die Informationen über 18674 verfügbare Bioproben enthielten, die von 29 deutschen Standorten gesammelt wurden. Ergebnisse: In den N=1095 ausgewerteten Datensätzen betrug das Verhältnis von Männern zu Frauen 1,8:1 mit Spitzenwerten bei 65-69 und 80-84 Jahren bei Männern und >85 Jahren bei Frauen. Die Analyse der Sequenz der unmittelbar zum Tod führenden Ereignisse ergab, dass in 86 % der Obduktionsfälle COVID-19 die zugrunde liegende Todesursache war, während in 14 % der Fälle COVID-19 eine Begleiterkrankung war. Die häufigste unmittelbare Todesursache war der diffuse Alveolarschaden, gefolgt von Multiorganversagen. Das Register unterstützt mehrere wissenschaftliche Projekte, die Öffentlichkeitsarbeit und liefert Berichte an die Bundesgesundheitsbehörden, was zu einer Anpassung des deutschen Infektionsschutzgesetzes führte und die Durchführung von Obduktionen in Pandemien erleichtert. Interpretation: Ein nationales Obduktionsregister kann multizentrische quantitative Informationen über COVID-19-Todesfälle auf nationaler Ebene liefern und damit die medizinische Forschung, die politische Entscheidungsfindung und die öffentliche Diskussion unterstützen. Finanzierung: Bundesministerien für Bildung und Forschung und für Gesundheit.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Autopsy; Cause of Death; COVID-19; Registry; SARS-CoV-2

Harnblase: Tumorvorstufen und nichtinvasive Karzinome - Lange, Fabienne; Hartmann, Arndt; Eckstein, Markus (Die Pathologie, 2024)
Background: In recent years, our understanding of the genesis and development of urothelial carcinomas (UC) has expanded considerably thanks to advancing molecular classifications. These advances have led to significant changes in the 5th edition of the WHO classification of tumors of the urinary tract and male genitalia. The new findings allow both the introduction of modern diagnostic approaches and a return to proven methods in the evaluation of precursor lesions and non-invasive carcinomas. Aims: This article is intended to provide a summarized overview of the various precursor lesions and pathways of urothelial carcinoma. Results and discussion: The changes and clarifications in the 5th edition of the WHO classification reflect the progress made in the molecular and morphological characterization of urothelial carcinomas. These adjustments provide an improved basis for diagnosis and treatment and emphasize the importance of differentiated molecular profiles for the classification and treatment of UC. Despite all this, conventional histology remains the gold standard for the diagnosis and classification of non-invasive carcinomas and precursor lesions.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Carcinoma in situ; Immunohistochemistry; Papillary carcinoma; Prognosis; Transitional cell carcinoma

Heterogeneity-analysis of molecular subtypes of muscle-invasive bladder cancer and their precursor lesions in multiregion mapped whole-organ bladders - Weyerer, Veronika; Lange, Fabienne; Wullweber, Adrian; Stöhr, Robert; Bertz, Simone; Wach, S.; Taubert, Helge; Wullich, Bernd; Sikic, Danijel; Strissel, Pamela; Strick, Reiner; Hartmann, Arndt; et al. (UROLOGIC ONCOLOGY-SEMINARS AND ORIGINAL INVESTIGATIONS, 2020)
CRIS-Team WoS Importer:2021-01-15

HLA-G expression associates with immune evasion muscle-invasive urothelial cancer and drives prognostic relevance - Branz, Annalena; Matek, Christian; Lange, Fabienne; Bahlinger, Veronika; Klümper, Niklas; Hölzel, Michael; Strissel, Pamela; Strick, Reiner; Sikic, Danijel; Wach, Sven; Taubert, Helge; Wullich, Bernd; et al. (Frontiers in Immunology, 2024)
Introduction: Urothelial bladder cancer is frequent and exhibits diverse prognoses influenced by molecular subtypes, urothelial subtype histology, and immune microenvironments. HLA-G, known for immune regulation, displays significant membranous expression in tumor tissues. Methods: We studied the protein expression of Human Leucocyte Antigen G (HLA-G) in 241 Muscle-Invasive Bladder Cancer (MIBC) patients, elucidating its potential clinical and biological significance. Protein expression levels were evaluated and correlated with molecular subtypes, histological characteristics, immune microenvironment markers, and survival outcomes. Results: High HLA-G expression associates with poor overall survival (OS) and diseasespecific survival (DSS), independent of clinicopathological parameters. HLA-G expression varies among molecular subtypes and Urothelial Subtype Histology, e.g., elevated expression levels in basal/squamous MIBC and those with sarcomatoid differentiation. Notably, HLA-G is increased in MIBC with an immune evasive microenvironment (high PD-L1 tumor cell expression, NK cell depletion, granzyme B (GZMB)/CD8 ratio reduction, MHC class I (MHCI) expression reduction) that are characterized by immunosuppressive features and poor prognosis. Furthermore, HLA-G correlates with elevated levels of other immune checkpoint proteins (TIGIT, LAG3, CTLA-4), indicating its role in immune evasion. Discussion: Our findings underscore HLA-G’s role as a potential prognostic marker and interesting immunotherapeutic target in MIBC. Its impact on immune evasion mechanisms and broad expression, coupled with associations withpoor survival and distinct tumor phenotypes, positions HLA-G as a promising protein for further exploration in developing targeted immunotherapies for MIBC patients.
CRIS-Team Scopus Importer:2024-11-15
Keywords: HLA-G; immune checkpoints; immune evasion; immune microenvironment; urothelial cancer

Immune Cell Gene Expression Signature is Associated with Improved Outcome in Muscle-Invasive Urothelial Bladder Cancer Patients Treated with Radical Cystectomy - Eckstein, Markus; Strissel, Pamela; Strick, Reiner; Weyerer, Veronika; Wirtz, Ralph M.; Pfannstiel, Carolin; Wullweber, Adrian; Lange, Fabienne; Erben, Philipp; Stöhr, Robert; Bertz, Simone; Geppert, Carol-Immanuel; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Integration of spatial pd-l1 expression with the tumor immune microenvironment outperforms standard pd-l1 scoring in outcome prediction of urothelial cancer patients - Weyerer, Veronika; Strissel, Pamela; Strick, Reiner; Sikic, Danijel; Geppert, Carol-Immanuel; Bertz, Simone; Lange, Fabienne; Taubert, Helge; Wach, Sven; Breyer, Johannes; Bolenz, Christian; Erben, Philipp; et al. (Cancers, 2021)
Background: Immune therapy has gained significant importance in managing urothelial cancer. The value of PD-L1 remains a matter of controversy, thus requiring an in-depth analysis of its biological and clinical relevance. Methods: A total of 193 tumors of muscle-invasive bladder cancer patients (MIBC) were assessed with four PD-L1 assays. PD-L1 scoring results were correlated with data from a comprehensive digital-spatial immune-profiling panel using descriptive statistics, hierarchical clustering and uni-/multivariable survival analyses. Results: PD-L1 scoring algorithms are heterogeneous (agreements from 63.1% to 87.7%), and stems from different constellations of immune and tumor cells (IC/TC). While Ventana IC5% algorithm identifies tumors with high inflammation and favorable baseline prognosis, CPS10 and the TCarea25%/ICarea25% algorithm identify tumors with TC and IC expression. Spatially organized immune phenotypes, which correlate either with high PD-L1 IC expression and favorable prognosis or constitutive PD-L1 TC expression and poor baseline prognosis, cannot be resolved properly by PD-L1 algorithms. PD-L1 negative tumors with relevant immune infiltration can be detected by sTILs scoring on HE slides and digital CD8+ scoring. Conclusions: Contemporary PD-L1 scoring algorithms are not sufficient to resolve spatially distributed MIBC immune phenotypes and their clinical implications. A more comprehensive view of immune phenotypes along with the integration of spatial PD-L1 expression on IC and TC is necessary in order to stratify patients for ICI.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Bladder cancer; Immune phenotypes; PD-1; PD-L1; TILs; Urothelial cancer

Intracranial hemorrhage in COVID-19 patients during extracorporeal membrane oxygenation for acute respiratory failure: a nationwide register study report - von Stillfried, Saskia; Bülow, Roman David; Röhrig, Rainer; Meybohm, Patrick; Boor, Peter; Böcker, Jana; Schmidt, Jens; Tholen, Pauline; Majeed, Raphael; Wienströer, Jan; Weis, Joachim; Bremer, Juliane; et al. (Critical Care, 2022)
Background: In severe cases, SARS-CoV-2 infection leads to acute respiratory distress syndrome (ARDS), often treated by extracorporeal membrane oxygenation (ECMO). During ECMO therapy, anticoagulation is crucial to prevent device-associated thrombosis and device failure, however, it is associated with bleeding complications. In COVID-19, additional pathologies, such as endotheliitis, may further increase the risk of bleeding complications. To assess the frequency of bleeding events, we analyzed data from the German COVID-19 autopsy registry (DeRegCOVID). Methods: The electronic registry uses a web-based electronic case report form. In November 2021, the registry included N = 1129 confirmed COVID-19 autopsy cases, with data on 63 ECMO autopsy cases and 1066 non-ECMO autopsy cases, contributed from 29 German sites. Findings: The registry data showed that ECMO was used in younger male patients and bleeding events occurred much more frequently in ECMO cases compared to non-ECMO cases (56% and 9%, respectively). Similarly, intracranial bleeding (ICB) was documented in 21% of ECMO cases and 3% of non-ECMO cases and was classified as the immediate or underlying cause of death in 78% of ECMO cases and 37% of non-ECMO cases. In ECMO cases, the three most common immediate causes of death were multi-organ failure, ARDS and ICB, and in non-ECMO cases ARDS, multi-organ failure and pulmonary bacterial ± fungal superinfection, ordered by descending frequency. Interpretation: Our study suggests the potential value of autopsies and a joint interdisciplinary multicenter (national) approach in addressing fatal complications in COVID-19.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Autopsy; Bleeding events; COVID-19; ECMO; Intracranial bleeding; Registry

Prognostic impact of molecular muscle-invasive bladder cancer subtyping approaches and correlations with variant histology in a population-based mono-institutional cystectomy cohort - Weyerer, Veronika; Stöhr, Robert; Bertz, Simone; Lange, Fabienne; Geppert, Carol-Immanuel; Wach, Sven; Taubert, Helge; Sikic, Danijel; Wullich, Bernd; Hartmann, Arndt; Eckstein, Markus (World Journal of Urology, 2021)
Purpose Recently discovered molecular classifications for urothelial bladder cancer appeared to be promising prognostic and predictive biomarkers. The present study was conducted to evaluate the prognostic impact of molecular subtypes assessed by two different methodologies (gene and protein expression), to compare these two approaches and to correlate molecular with histological subtypes in a consecutively collected, mono-institutional muscle-invasive bladder cancer (MIBC) cohort. Methods 193 MIBC were pathologically re-evaluated and molecular subtypes were assessed on mRNA (NanoString technology, modified 21-gene-containing MDACC approach) and protein levels (immuno-histochemical [IHC] analysis of CK5, CK14, CD44, CK20, GATA3 and FOXA1). Descriptive statistical methods and uni-/multi-variable survival models were employed to analyze derived data. Results Neither gene expression nor protein-based subtyping showed significant associations with disease-specific (DSS) or recurrence-free survival (RFS). Agreement between mRNA (reference) and protein-based subtyping amounted 68.6% for basal, 76.1% for luminal and 50.0% for double-negative tumors. Histological subtypes associated with RFS in uni-variable (P = 0.03), but not in multivariable survival analyses. Tumors with variant histology predominantly showed luminal subtypes (gene expression subtyping: 36/55 cases, 65.5%; protein subtyping: 44/55 cases, 80.0%). Squamous differentiation significantly associated with basal subtypes (gene expression subtyping: 44/45 squamous cases, 97.8%; protein subtyping: 36/45 cases, 80.0%). Conclusion In our consecutive cystectomy cohort, neither gene, protein expression-based subtyping, nor histological subtypes associated with DSS or RFS in multi-variably adjusted survival analyses. Application of a limited IHC subtyping marker panel showed high concordance of 83.9% with gene expression-based subtyping, thus underlining the utility for subtyping in pathological routine diagnostics. In addition, histological MIBC subtypes are strong indicators for intrinsic subtypes.
CRIS-Team WoS Importer:2021-07-23

Tert promoter mutation analysis of whole-organ mapping bladder cancers - Weyerer, Veronika; Eckstein, Markus; Strissel, Pamela; Wullweber, Adrian; Lange, Fabienne; Tögel, Lars; Geppert, Carol-Immanuel; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Hartmann, Arndt; et al. (Genes, 2021)
Background: Multifocal occurrence is a main characteristic of urothelial bladder cancer (UBC). Whether urothelial transformation is caused by monoclonal events within the urothelium, or by polyclonal unrelated events resulting in several tumor clones is still under debate. TERT promoter mutations are the most common somatic alteration identified in UBC. In this study, we analyzed different histological tissues from whole-organ mapping bladder cancer specimens to reveal TERT mutational status, as well as to discern how tumors develop. Methods: Up to 23 tissues from nine whole-organ mapping bladder tumor specimens, were tested for TERT promoter mutations including tumor associated normal urothelium, non-invasive urothelial lesions (hyperplasia, dys-plasia, metaplasia), carcinoma in situ (CIS) and different areas of muscle invasive bladder cancers (MIBC). The mutational DNA hotspot region within the TERT promoter was analyzed by SNaPshot analysis including three hot spot regions (−57, −124 or −146). Telomere length was measured by the Relative Human Telomere Length Quantification qPCR Assay Kit. Results: TERT promoter mutations were identified in tumor associated normal urothelium as well as non-invasive urothelial lesions, CIS and MIBC. Analysis of separate regions of the MIBC showed 100% concordance of TERT promoter mutations within a respective whole-organ bladder specimen. Polyclonal events were observed in five out of nine whole-organ mapping bladder cancers housing tumor associated normal urothelium, non-invasive urothelial lesions and CIS where different TERT promoter mutations were found compared to MIBC. The remaining four whole-organ mapping bladders were monoclonal for TERT mutations. No significant differences of telomere length were observed. Conclusions: Examining multiple whole-organ mapping bladders we conclude that TERT promoter mutations may be an early step in bladder cancer carcinogenesis as supported by TERT mutations detected in tumor associated normal urothelium as well as non-invasive urothelial lesions. Since mutated TERT promoter regions within non-invasive urothelial lesions are not sufficient alone for the establishment of cancerous growth, this points to the contribution of other gene mutations as a requirement for tumor development.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Clonality; TERT promoter mutation; Whole-organ mapping bladder tumor

Utility of stromal tumor infiltrating lymphocyte scoring (sTILs) for risk stratification of patients with muscle-invasive urothelial bladder cancer after radical cystectomy - Sikic, Danijel; Weyerer, Veronika; Geppert, Carol-Immanuel; Bertz, Simone; Lange, Fabienne; Taubert, Helge; Wach, Sven; Schmitz-Draeger, Bernd J.; Wullich, Bernd; Hartmann, Arndt; Eckstein, Markus (Urologic Oncology-Seminars and Original Investigations, 2021)
Background: Multi-omics analyses of muscle-invasive bladder cancer (MIBC) demonstrated that specific patterns of tumor infiltrating lymphocytes (TILs) associates with improved outcomes in patients treated with radical cystectomy. However, methodologies for simple and robust quantification of TILs, especially for daily practice purposes, are lacking. Thus, we investigated the feasibility of stromal TIL scoring on hematoxylin/eosin stained (HE) slides in MIBC. Materials and methods: sTILs were scored on HE whole slides of 241 MIBC patients treated with radical cystectomy and adjuvant chemotherapy. Median infiltration of 10% was used as objective cut-off. Additionally, immunohistochemistry was performed on spatially organized tissue microarrays to quantify key immune cell populations objectively for correlational analyses with sTIL scoring results (CD3+/Pan-T-cells, CD8+/cytotoxic T-Cells, CD56+/NK-cells, CD68+/macrophages). sTILs amounts were correlated with clinicopathological features, recurrence-free (RFS), disease-specific (DSS), and overall survival (OS). Results: sTIL amounts correlated moderately to strongly with quantitatively estimated amounts of pan-T-cells (r = 0.73, P <0.0001), cytotoxic T-cells (r = 0.73, P <0.0001), NK-cells (r = 0.68, P <0.0001), macrophages (r = 0.55, P <0.0001) and with pan-cytotoxic immune infiltration (r = 0.78, P <0.0001), thus reflecting overall infiltration with key immune cell populations. sTIL infiltration ≥10% was associated with significantly higher 5-year OS (45.5% vs. 19.8%), DSS (56.6% vs. 25.6%) and RFS (56.2% vs. 18.9%; P <0.0001 for all three comparisons) rates, and lower pT-stage (P = 0.015), lower pN-stage (P = 0.028), lower rates of lymphovascular invasion (P = 0.0003) and blood vessel invasion (P = 0.01) when compared to sTIL infiltration of <10%. Multivariable regressions models confirmed sTILs as strongest independent predictor for improved outcomes following radical cystectomy. Conclusions: HE based sTIL scoring is a reliable tool to assess MIBC inflammation status and to stratify the survival of MIBC patients undergoing radical cystectomy. sTIL amount is an independent predictor for improved survival, and might be an useful, routinely applicable tool to identify patients benefiting from perioperative platinum-based chemotherapy and checkpoint inhibitor therapy. However, external validation of our data is required.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Bladder cancer; Cystectomy; Prognosis; sTILs; TILs; Urothelial cancer